Pulmonary Complications of Sickle Cell Disease - Miller, Andrew C. (American Thoracic Society, 2012)
Sickle cell disease (SCD) is a common monogenetic disorder with high associated morbidity and mortality. The pulmonary complications of SCD are of particular importance, as acute chest syndrome and pulmonary hypertension have the highest associated mortality rates within this population. This article reviews the pathophysiology, diagnosis, and treatment of clinically significant pulmonary manifestations of SCD, including acute chest syndrome, asthma, and pulmonary hypertension in adult and pediatric patients. Clinicians should be vigilant in screening and treating such comorbidities to improve patient outcomes.